Staff supported community outings among forensic mental health patients: patient characteristics, rehabilitative goals, and (the absence of) adverse outcomes - Farrell, Christian; Petersen, Karen L.; Hanzouli, Peri; Nicholls, Tonia L. (Frontiers in Psychiatry, 2024)
Mental health professionals are tasked with making difficult clinical decisions in treatment settings. In the forensic system, decision making regarding staff supervised community outings (SSCOs) provides a significant challenge due to the need to balance patient liberties, mental health recovery, and public safety. This study explored the characteristics and rehabilitative nature of SSCOs, characteristics of patients attending SSCOs, and any adverse events that occurred during the outings. Employing a cross-sectional design, 110 patients who participated in SSCOs over a one-year period from a Canadian Forensic Psychiatric Hospital were included. Clinical records were reviewed to capture patient and SSCO variables. Descriptive analyses were used to calculate participant, risk, SSCO, and adverse event characteristics. Qualitative analysis was used to explore the purpose of SSCOs and rehabilitative progress that occurred during the outings. Patients attending SSCOs were comprised of long-stay patients with over half having committed a violent index offence. Almost 75% of patients had a moderate/high risk for violence and 50% of the patients had a moderate/high risk of absconding. During the study period, 463 SSCOs were completed. Most outings focused on developing skills for daily living and staff comments suggested many patients developed skills in these areas. Despite considerable risk profiles and public concern regarding forensic patients having community access, there was a single occurrence of unauthorized leave and no instances of violence or substance use. This research can disrupt stigma, demonstrating that SSCOs support a specific rehabilitative intent, promote community reintegration, and maintain public safety.